Implications of municipal solid waste management on greenhouse gas emissions in Malaysia and the way forward. (1st January 2021) - Michel Devadoss, P.S.; Agamuthu, P.; Mehran, S.B.; Santha, C.; Fauziah, S.H.
Highlights: According to IPPC 2006, landfills released 6, 898, 167 tonnes CO2 -eq of GHG emissions. Overall MSW management released 15, 906, 614 tonnes CO2 -eq of GHG emissions. Integrated approach will reduce more GHG emissions than recycling or incineration. Recycling will reduce more GHG emissions than incineration. Abstract: The management of municipal solid waste (MSW) in Malaysia has been mainly focused on collection, transportation and disposal of MSW. To examine the contribution of MSW management to GHG emissions, Intergovernmental Panel on Climate Change (IPCC) 2006 Waste Model was used by deploying Tier 2 method. It estimated that 6, 898, 167 tonnes CO2 -eq of GHG emissions were released in 2016 from solid waste disposal sites (SWDS) and are projected to increase to 9, 991, 486 tonnes CO2 -eq in 2030. To reduce GHG emissions from MSW management, Solid-Waste-Management Greenhouse-Gas (SWM-GHG) calculator was used to compare different approaches. SWM-GHG calculator focused on three settings including recycling approach, incineration approach and integrated approach. According to SWM-GHG calculator, in 2016, 15, 906, 614 tonnes CO2 -eq of GHG emissions were released by recycling approximately 16% of MSW and disposing of 84% of MSW in SWDS. Out of the three approaches, integrated approach can result in highest reduction of GHG emissions by 2050 (64%) from GHG emissions in 2016, as compared to recycling approach (50% reduction) and incineration approach (46% reduction). While, recycling has been the main national goal for last 14 years as it has increased up to 17.5% by 2016, the current Malaysian government aims to establish 8 incinerators in Malaysia that will treat approximately 32% of MSW annually. However, estimations of SWM-GHG calculator and some opportunities and threats highlighted by SWOT analysis suggest the integrated approach as the best suited approach for Malaysia for achieving significant and sustainable reductions in GHG emissions.